Effect of Indian Medicinal Plants Extract against Isolated Bacteria Common Responsible for Food Spoilage Microorganism - Akanksha,; Dr. Puneet,; Gurinder Singh,; Harpreet Kaur, (International Journal of Scientific Research in Science and Technology, 2025)
The ongoing quest for novel antimicrobial agents to combat the threat posed by resistant microbes is essential to the effectiveness of food quality control. Using the disc diffusion method, the ethanol extracts of five medicinal spices (spinach, coriander, orange peel, fenugreek, and turmeric) that are used in Indian homes as flavor enhancers were examined for in vitro antibacterial activity against Salmonella typhi, a foodborne pathogen. Among all the examined bacterial isolates, ethanol extracts of coriander exhibited the strongest antibacterial activity (55 mm), whereas extracts of spinach exhibited the lowest activity (22 mm). These five extracts were tested against organism to determine their minimum inhibitory concentration (MIC). At the Higher concentration, ethanol-orange peel demonstrated the strongest antibacterial activity against the test microorganisms, whereas Ethanol-Turmeric showed the lowest antimicrobial activity against the experimental organism. Biuret, Fehling, Benedict’s, Ferric chloride, Mayers, and Dragendroff’s tests of phytochemical of all extracts were showed positive effect.
Keywords: Plant Extracts; Antimicrobial susceptibility; Minimum Inhibition concentration; orange peel; turmeric powder